Study of novel 1,4-dihydropyridine derivatives as prospective anti-inﬂammatory remedies: a randomised controlled trial - E. Yu. Bibik; D. S. Krivokolysko; G. A. Batishcheva; A. A. Samokish; Yu. S. Venidiktova; A. V. Myazina; A. A. Pankov; K. A. Frolov; V. V. Dotsenko; S. G. Krivokolysko (Кубанский научный медицинский вестник, 2022)
Background. Over the past decades, scientiﬁc community is motivated on ﬁnding new anti-inﬂammatory agents with a safe and high-effective proﬁle to manage pathology.Objectives. A study of the anti-inﬂammatory action of novel compounds, 1,4-dihydropyridine derivatives, in a classical formalin-induced paw oedema test in white rats.Methods. Originally synthesised 1,4-dihydropyridine derivatives were preliminarily subjected to virtual screening using the SwissTargetPrediction toolkit. White laboratory rats (130 animals) were divided into a control (formalin oedema) and intact group, 4 comparison (meloxicam, sodium metamizole, sodium diclofenac and indomethacin) and 7 experiment groups by the number of 1,4-dihydropyridine derivatives studied. The samples anti-inﬂammatory efﬁcacy was evaluated in acute formalin-induced paw oedema model simulated by right hind limb subplantar injection of 0.1 mL 2% formalin. The studied substances were administered intragastrically at 5 mg/kg 1.5 h prior to oedema induction. Oncometry was assessed quantitatively by limb circumference. Animals were managed in compliance with GOST 33044–2014 “Principles of Good Laboratory Practice” at all experiment steps. Experimental data were analysed statistically to describe quantitative variability with variance σ2, mean limb girth a and standard deviation σ. Data homogeneity and reliability were estimated by variation coefﬁcient V and the Wilcoxon T(W) criterion.Results. As the most anti-inﬂammatory effective, partially hydrogenated mar-040 pyridines (ethyl 4-({[5-cyano-6-{[2-(diphenylamino)-2-oxoethyl]thio}-4-(2-furyl)-2-methyl-1,4-dihydropyridin-3-yl]carbonyl}amino) benzoate) were shown 33-fold superior to indomethacin, 26-fold — to sodium diclofenac, 25-fold — to meloxicam and 30-fold — to sodium metamizole; mar-037 pyridines (ethyl 4-[({[3-cyano-5-({[4-(ethoxycarbonyl)phenyl]amino}carbonyl)-4-(2-furyl)-6-methyl-1,4-dihydropyridin-2-yl]thio}acetyl)amino] benzoate) — 17–23-fold superior vs. reference drugs. We also show that mаr-014 (ethyl 4-({[5-cyano-6-({2-[(3,5-dichlorophenyl) amino]-2-oxoethyl}thio)-4-(2-furyl)-2-methyl-1,4-dihydropyridin-3-yl]carbonyl}amino)benzoate) and mar033 (ethyl 2-[({[3-cyano-5-({[4-(ethoxycarbonyl)phenyl]amino}carbonyl)-4-(2-furyl)-6-methyl-1,4-dihydropyridin-2-yl]thio}acetyl)amino]-4,5,6,7-tetrahydro-1-benzothiophene-3-carboxylate) compounds are 2.7-fold more effective vs. reference drugs.Conclusion. The synthesised 1,4-dihydropyridine compounds reveal high efﬁcacy in experimental assays. Selected novel 1,4-dihydropyridine derivatives exhibit a marked anti-inﬂammatory activity and offer value in future preclinical trials.